Method of measuring doppler shift of moving targets using FMCW maritime radar - Sediono, Wahju (2013)
During the operation of an FMCW (frequency modulated continuous wave) maritime radar, the system transmits a continuous radio energy with a frequency modulated by a triangular or sawtooth-shaped signal. As a result, the frequency of the transmitted signal varies gradually with time. When the signal is reflected by an object, the received waveform will build up a delayed replica of the transmitted waveform, with the time delay as a measure of the target range. If the target is moving, the radar system will register a Doppler shift within the received signal. Compared to the frequency of the emitted signal, the received signal will show a higher frequency when the target is approaching and a lower frequency when the target is moving away from the radar location. Thus, the total Doppler shift may result from the superposition of both source and observer motions. Specifically, the amount of Doppler shift is directly proportional to the radial speed of the target. The Doppler shift can be determined after performing the range Fourier transform (range FFT) first. For a target of interest, we can repeat the range FFT until we have enough data to perform the second level of FFT. The result of this second FFT is a two dimensional complex valued matrix, whose spectral peak corresponds to the Doppler shift of the moving target. This method is known as Doppler FFT. Some results of the measurement of target speed using this method are presented in this paper.